Identification And Characterization Of A Novel Anti-Viral Peptide Against Avian Influenza Virus H9n2 - Rajik, Mohamed (2009)

(untitled)
Avian influenza viruses (AIV) are major cause of morbidity and mortality in the world. It is the causative agent of the most dangerous disease, called bird flu in common terms, among poultries. This virus belongs to the family of Orthomyxoviridae which contains two genera, influenza A & B and influenza C. Although avian influenza A viruses do not usually infect humans, several instances of human infections and outbreaks have been reported. Spanish flu, the well known influenza pandemic of 1918, is thought to have killed more than 50 million people worldwide. Although vaccination is the primary strategy for the control of infection, the antiviral drugs play an important role in the control of illness and transmission. Two classes of antiviral drugs are recommended for the treatment of influenza infection. They are adamantane derivatives (amantadine and rimantadine) and neuraminidase inhibitors (NAIs; zanamivir and oseltamivir). The rate of adamantane resistance has increased significantly from below 2% to an alarming 92.3% in recent years. Few viruses with altered susceptibility to NAIs have also been isolated from the infected people. Several recent H5N1 influenza isolates recovered from the patients showed resistance to both classes of antiviral drugs. The increasing appearance of resistant strains of influenza virus and side effects of the currently available chemotherapeutic agents emphasises our need to identify new antiviral drugs. In order to identify novel antiviral drugs, phage display library was utilised in this study. They were biopanned against the purified avian influenza virus H9N2. After four rounds of biopanning, four unique recombinant fusion phages bearing different peptide sequences were isolated. Their binding specificity was confirmed by modified phage-ELISA method. Among the four peptides, the peptide denoting the sequence NDFRSKT (P1) was taken into account for further analysis as it showed a high percentage of presence after the fourth round of panning and good inhibitory properties. The in vitro inhibitory properties of the fusion phages were proved by the ability of the phage molecules to stop the multiplication of the virus in MDCK cell lines whereas, the in ovo inhibition ability of both peptides and fusion phages were assessed using the 9 days old embryonated chicken eggs. The antiviral molecule’s ability to inhibit the hemagglutination activity and neuraminidase (NA) activity were also investigated using conventional hemagglutination inhibition test and neuraminidase inhibition test respectively. They were able to inhibit the HA activity but failed to inhibit the neuraminidase activity completely. The antibody-phage competition assay showed that the peptide molecule share some common epitopes of the viral surface proteins for their binding site. In order to investigate the in vivo binding ability of the molecules inside a cellular environment and to identify the binding domain on the viral proteins, the peptide and virus surface glycoproteins interaction were analysed by the yeast two-hybrid system. The results showed that the C-terminal region of the HA protein was responsible for the interaction with the peptide. This was further confirmed by the co-immunoprecipitation experiment. To understand the mechanism of the drug action, the effect of drug on the viral attachment and the viral entry to the host cell (MDCK cells) was studied by fluorescence microscopy and flow cytometry. The study revealed that the peptides prevent the attachment of the virus to the host cells, confirming the result of earlier haemagglutination inhibition experiment. Besides, it was also found that the peptides inhibit the early gene expression. But the peptides do not have any effect on preventing the entry of the virus molecules. In summary, the current study had identified a novel antiviral peptide which inhibits the AIV H9N2 multiplication in ovo and in vitro, by binding the HA. This peptide prevents the attachment of the virus to the host cells thereby preventing its internalisation and early protein expressions. These new antiviral molecules may have the potential to control and treat the avian influenza virus infected individuals.